Two‐generational effects of contaminants in Daphnia magna: Effects of offspring quality. (18th March 2016) - Campos, Bruno; Jordão, Rita; Rivetti, Claudia; Lemos, M.F.L.; Soares, A.M.V.M.; Tauler, Roma; Barata, Carlos
Abstract: The authors set up a protocol to perform a 2‐generational ring test using the existing guidelines for the Daphnia magna reproduction test. It is well known in ecology that size and quality of offspring vary across the first clutches in D. magna and that certain chemicals affect offspring quality. Therefore, the origin of the second generation is an important factor to consider. Two‐generational effects across first, second, and third clutches were evaluated using 4‐nonylphenol; those across first and third clutches were evaluated using tributyltin, and those across the third clutch were evaluated using piperonyl butoxide. The compound showing the greatest aggravation of toxic effects between the parental and second generations was piperonyl butoxide, followed by 4‐nonylphenol, whereas intergenerational effects of tributyltin varied across experiments. The studied chemicals affected the quantity and quality of the offspring produced by exposed females of the parental generation, those effects being greater in third‐clutch neonates. Therefore, when third‐clutch offspring were further exposed, they turned out to be more sensitive than the parental generation. The results are in line with those obtained in multigenerational studies using mammalian tests, which showed that, in many cases, effects on the second generation can be predicted by evaluating the quality of the offspring produced. Environ Toxicol Chem 2016;35:1470–1477. © 2015 SETAC